THE IMPORTANCE OF STUDYING THE METHODOLOGY OF TEACHING THE AMINO ACIDS MODULE BASED ON A CREATIVE APPROACH. - Reymov, Qarjaubay Davletbayevich; Kadirova, Risolat Soatboevna (SCIENCE and SOCIETY, 2026)
This scientific article highlights the importance, substantive foundations, modern methods, and impact of creative pedagogical approaches in teaching the amino acid module. The study analyzes pedagogical strategies aimed at developing independent thinking, an analytical approach, and chemical thinking in students, based on the role of innovative educational technologies in the educational process. The content of the article has been revised and structured based on an original approach to avoid duplication of materials from the Internet.